Respon Tanaman Kedelai terhadap Serapan Hara NPK Pupuk Daun yang diberikan Melalui Akar dan Daun pada Tanah Gambut dan Podsolik - Fitriadi Yusuf; Jamzuri Hadie; Muhammad Fadly H Yusran (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2017)
The objectives of this study were to study: 1) to analyze the response of soybean crops to nutrient uptake of NPK in leaf fertilizer given through spraying of leaves and soil passing through plant roots, 2) to analyze the effectiveness between the two ways of applying leaf fertilizer to soybean plants on peat soil and mineral soil. The study was conducted for four months in March until June 2014. The research was conducted at the location of the Faculty of Agriculture and Forestry of Muhammadiyah University of Palangkaraya. The results of the study indicated that: 1) the interaction between the soil type and the application of the liquid fertilizer no significant effect on N uptake in stem + leaf, P uptake in stem + leaf, and K uptake in stem + leaf; 2) liquid NPK fertilizers (NASA) supplied by leaf and soil showed a slightly different response to soybean crops planted on both soil types, and their contribution to growth growth and crop production compared to non-fertilized ones (